Diversidade e caracterização de espécies de Colletotrichum associadas a Annona spp - Almeida, Cláudia Alves de (2015)
Anthracnose, caused by Colletotrichum species, occurs in various fruit of tropical and temperate. In Brazil is the main disease of Annonaceae. We evaluated the diversity of species of Colletotrichum in association with species of Annona through multigene phylogenetic analysis, evaluation of morphological characters and culture and pathogenicity test. 84 isolates were obtained from fruits, flowers and leaves showing anthracnose, and mummified fruits of commercial and native species collected in commercial plantations and orchards. Partial sequences of the GAPDH gene of 31 isolates of Colletotrichum were analyzed by the Maximum Parsimony method (MP). Based on the generated clusters and geographical origin was selected a subset of fourteen isolates are analyzed for the partial sequences of ACT and TUB2 genes as well as for the combined analysis of the three gene regions performed by Bayesian inference method and MP. The same fourteen isolates were also characterized based on morphology of conidia and appressoria, mycelial growth rate (TCM), colony color and used in pathogenicity tests in sweetsop seedlings. Five species were identified: C. fructicola, C. theobromicola, C. gloeosporioides stricto sensu in the complex ‘gloeosporioides’; C. nymphaeae in the complex ‘acutatum’; and C. karstii in the complex ‘boninense’. Other five isolates couldn’t be resolved phylogenetically. This is the first report of C. fructicola, C. nymphaeae and C. karstii in Annonaceae in Brazil. The morphological characters were not informative enough for separating complex and species. All fourteen Colletotrichum evaluated were pathogenic to Annona squamosa, causing typical symptoms of anthracnose on the leaves. The correct identification of these species will be useful in epidemiological studies and in breeding programs, thus contributing to the correct and efficient management of the disease, minimizing the losses caused by the pathogen in the pre and post-harvest.